Análise do transcriptoma de Corynebacterium pseudotuberculosis em resposta à limitação por ferro - Izabela Coimbra Ibraim (2018)
The ciuA gene codes for a surface protein which is associated to a siderophore-base iron acquisition system; however, its role in the acquisition of iron in C. pseudotuberculosis is still largely unknown. Iron is crucial for the growth and development of many bacterial pathogens; however, within the host, the concentration that is freely accessible is much lower than the concentration required for bacterial growth. In intracellular bacteria, like C. pseudotuberculosis, iron homeostasis is transcriptionally controlled by the availability of iron in the environment, which allows the bacteria to counteract the limitation of the metal imposed by the host. In a previous work conducted by our group, we described the construction of a ciuA gene mutant strain (Cp13), generated by using the in vivo insertional mutagenesis of the reporter transposon-based system TnFuZ in the T1 strain of C. pseudotuberculosis. The disruption of the ciuA gene led to a decrease in virulence and intracellular viability of the mutant strain. In addition, immunization of mice with the Cp13 strain elicited significantly IgG titers and higher survival rate (80%). The ciuA gene codes for a surface protein which is associated to a siderophore-base iron acquisition system; however, its role in the acquisition of iron in C. pseudotuberculosis is still largely unknown. Iron is crucial for the growth and development of many bacterial pathogens; however, within the host, the concentration that is freely accessible is much lower than the concentration required for bacterial growth. In intracellular bacteria, like C. pseudotuberculosis, iron homeostasis is transcriptionally controlled by the availability of iron in the environment, which allows the bacteria to counteract the limitation of the metal imposed by the host. Herein, our primary goal was to comprehensively characterize the transcriptional response of C. pseudotuberculosis under iron restriction. Differential gene expression analyses of the wild-type strain (T1 strain) and the (ciuA) Cp13 mutant strain (Cp13 strain) were conducted in low iron (LI) cultures, supplemented with the iron-chelator 2,2’-dipyridyl-DIP, in relation to high iron (HI) cultures in both strains. In this context, the data presented here shows a significant reduction in cellular density and the growth rate of the Cp13 mutant strain in relation to the parental strain under iron restriction. In total, 120 and 86 differentially expressed genes (DEGs) were identified in the T1 and Cp13 strains in response to iron restriction, respectively. 36 of these genes were identified in both strains and 26 of these genes had a similar expression pattern in both strains. Two transcription factors, known to be regulated by DtxR, were also identified between the overlapped DEGs of both strains, indicating a complex regulatory network controlled by the availability of iron in C. pseudotuberculosis. Out of the 26 genes, 7 DEGs encode high-affinity hemin-binding proteins. Interestingly, 4 hemin-binding genes were identified located within genomic islands harboring known virulence factors, corroborating with the association of iron acquisition and virulence in pathogenic bacteria. We have also observed that the intracellular restriction of iron usage is key to the iron starvation response of C. pseudotuberculosis. Significant differences between mutant and parental strains were also observed in relation to the strain-specific DEGs, indicating divergence in the adaptive responses of the mutant and parental strains in response to iron restriction. Altogether, these findings provide a comprehensive analysis of the regulatory network and transcriptional response of the Cp13 mutant and T1 parental strain of C. pseudotuberculosis, adding relevant insights into the transcriptional adaptation of this important pathogen within an iron-restricted environment.